The required quality of electrical energy provision - A. A. Naumov (Известия высших учебных заведений: Проблемы энергетики, 2020)
Methods of the electrical energy (EE) with the required quality provision in conditions of limited financial opportunities in the power supplying companies (PSC) are being discussed considering the foreign countries experience. It is proposed to develop and apply tariffs differentiated by the degree of EE reliability and quality, in compliance with the EE quality required for definite consumers. As a result, both consumers and PSC may get the best of tariffs application differentiated by the quality level. Consumers with power receiving appliances not demanding the high quality of EE will gain profit from payment reduction, whereas the consumers with power receiving appliances demanding the high quality of EE – from successful operation of electrical appliances, increase of their operating time and high quality of manufactured products provision. PSC acquire incentives for EE quality management upon the consumers’ request, as well as opportunities of more efficient use of financial resources directed at different quality EE provision to the consumer.